Trade Liberalization and Manufacturing Productivity Changes in Korea during the Past Three Decades - Yeongkwan Song (KDI Journal of Economic Policy, 2021)
The main objective of this study is to determine whether there have been TFP increases in the Korean manufacturing sector due to trade liberalization since the 1990s. Based on the methodology proposed by Pavcnik (2002), which focuses on the channel through which trade liberalization measures enhance overall industrial productivity by triggering the exit of low-productivity firms, this study tests the following two hypotheses: first, the TFP increase in the Korean tradable industry is not higher than that in the non-tradable industry, and second, plants with lower TFP levels did not exit from the tradable industry. Through the rejection of these two hypotheses, it is possible to infer indirectly the effect of trade liberalization on firm productivity rates in Korea since the 1990s. First, this analysis reveals that since the 1990s, the TFP of the tradable sector compared to the non-tradable sector presented a statistically meaningful increase only in the 2000s, when China joined the WTO and trade increased sharply between Korea and China. Secondly, TFP growth in the tradable sector was positively affected by exits, as it was plants with lower TFP levels that ceased to exist.
Keywords: F13; F14; O3; 330; Trade Liberalization; Productivity; Exit